Responding to youth sexual offending: a field-based practice model that "closes the gap" on sexual recidivism among Indigenous and non-Indigenous males. Issue 1 (2nd January 2016) - Allard, Troy; Rayment-McHugh, Sue; Adams, Dimity; Smallbone, Stephen; McKillop, Nadine
Abstract: Most studies that have explored the impact of youth sexual offender treatment on recidivism have not assessed whether effectiveness varies for important subgroups. The present study evaluated the impact of treatment provided by the Griffith Youth Forensic Service (GYFS) on 104 adjudicated youth sexual offenders referred between 2006 and 2012. Sexual, violent and "other" offending outcomes were examined, based on Australian Indigenous cultural heritage and whether the youth resided in a remote community, over an average 2.5-year follow-up timeframe. The findings indicated that GYFS treatment was equally effective for Indigenous and non-Indigenous youth for preventing sexual recidivism and, for youth residing in remote and non-remote locations, for preventing sexual, violent and "other" recidivism. Treatment was less effective in preventing violent and "other" recidivism for Indigenous youth. The core components of the GYFS treatment programme therefore appear particularly well suited for reducing sexual recidivism by Indigenous offenders and those residing in remote communities.